2016
DOI: 10.1021/acs.jpcc.6b05667
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of Perovskite Solar Cell Using a Reduced-Graphene Scaffold

Abstract: Interface engineering of solar cell device is a prominent strategy to improve the device performance. Herein, we synthesize reduced-graphene scaffold (rGS) by using a new and simple chemical approach. In this regard, we synthesize a hollow structure of graphene and then fabricate a three-dimensional scaffold of graphene with a superior surface area using electrophoretic process. We employ this scaffold as an interface layer between the electron transfer and absorber layers in perovskite solar cell. The charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…Alternatively, reduced or chemically functionalized GO possesses a work function between −4.3 and −4.4 eV, which leads to well‐matched energy levels between the organic active layer and the anode. A schematic illustrating the energy level alignments of 2D–organic hybrid OPV structures with various GO derivatives is shown in Figure a . Silva and coworkers reported that a mixture of solution‐processed reduced GO and ZnO or TiO x is promising as an electron transport layer in PTB7/PCBM bulk heterojunction OPVs .…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, reduced or chemically functionalized GO possesses a work function between −4.3 and −4.4 eV, which leads to well‐matched energy levels between the organic active layer and the anode. A schematic illustrating the energy level alignments of 2D–organic hybrid OPV structures with various GO derivatives is shown in Figure a . Silva and coworkers reported that a mixture of solution‐processed reduced GO and ZnO or TiO x is promising as an electron transport layer in PTB7/PCBM bulk heterojunction OPVs .…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
“…The composite was synthesized via the noncovalent functionalization method. The dispersity of the composite was significantly improved, and consequently, it could easily be applied as an electron transport layer for enhancing the performance of P3HT/PCBM bulk heterojunction OPVs …”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
“…Energy level of each layer in PSCs . A, Energy loss exists when LUMO level of perovskite is much larger than that of ETL.…”
Section: Carbon Materials In Single‐junction Pscsmentioning
confidence: 99%
“…Graphene, a single layer of sp 2 ‐hybridized carbon atoms, has attracted extensive attention for its unique nanostructure and unusual properties, such as excellent electron mobility, high thermal conductivity, high specific surface area, excellent pliability, and high chemical stability. These properties enable graphene to become a promising material for applications of batteries, supercapacitors, field‐effect transistors, fuel cells, solar cells, sensors, and molecular sieving membranes . Graphene quantum dots (GQDs) and graphene oxide quantum dots (GOQDs), two members of the graphene family, possessing the advantage of graphene, are playing important roles in development and application of nanotechnology, such as bioimagings, fluorescent sensors, batteries, photocatalysts, light‐emitting diodes, photovoltaic devices, and drug delivery .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a single layer of sp 2 -hybridized carbon atoms, has attracted extensive attention for its unique nanostructure and unusual properties, such as excellent electron mobility, high thermal conductivity, high specific surface area, excellent pliability, and high chemical stability. These properties enable graphene to become a promising material for applications of batteries, [1] supercapacitors, [2] field-effect transistors, [3] fuel cells, [4] solar cells, [5] sensors, [6] and molecular sieving membranes. [7] Graphene oxide quantum dots (GOQDs) attract great attention for their unique properties and promising application potential.…”
Section: Introductionmentioning
confidence: 99%